Cluster Morphology of Colloidal Systems With Competing Interactions - Valadez-Pérez, Néstor E.; Liu, Yun; Castañeda-Priego, Ramón (Frontiers in Physics, 2021)
Reversible aggregation of purely short-ranged attractive colloidal particles leads to the formation of clusters with a fractal dimension that only depends on the second virial coefficient. The addition of a long-ranged repulsion to the potential modifies the way in which the particles aggregate into clusters and form intermediate range order structures, and have a strong influence on the dynamical and rheological properties of colloidal dispersions. The understanding of the effect of a long-ranged repulsive potential on the aggregation mechanisms is scientifically and technologically important for a large variety of physical, chemical and biological systems, including concentrated protein solutions. In this work, the equilibrium cluster morphology of particles interacting through a short-ranged attraction plus a long-ranged repulsion is extensively studied by means of Monte Carlo computer simulations. Our findings point out that the addition of the repulsive affects the resulting cluster morphology and allows one to have a full control on the compactness or fractal dimension of the aggregates at a given thermodynamic condition. This allows us to manipulate the reversible aggregation process and, therefore, to finely tune the resulting building blocks of materials at large length scales.